PENGARUH PENERAPAN SVLK, FSC, PEFC TERHADAP DAYA SAING INDUSTRI KERTAS DI JAWA TENGAH - Purwanto, Agus; Saifuddin, Mirza Prameswari; Kotamena, Fredson; Asbari, Masduki; Santoso, Priyono Budi; Ramdan, Mohamad; Sulistiyadi, Andi; Wijayanti, Laksmi Mayesti; Hyun, Choi Chi; Sihite, Otto Berman; Pramono, Rudy (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2020)
The purpose of this study was to determine the effect of the SVLK Timber Legality and Verification System, FSC Chain of Custody, PEFC Sustainable Forest Management for wood and wood-based products on the competitiveness of the wood industry in Central Java. This research was conducted in several companies that process wood or use wood as the main material in Central Java with a total of 300 respondents. The respondents of this study are wood industry employees as top management, managers and staff who have been implementing SVLK, FSC, PEFC for at least 2 years. The background of this study is due to the lack of PEFC, FSC and SVLK research on the wood industry in Indonesia's Central Java province. Data collection was carried out by distributing electronic questionnaires online during January 2020 and analyzing data processing using Structural Equation Model (SEM) and Linear Structural Model (LISREL) software version 8.70. The analysis shows that the application of SVLK, FSC Chain of Custody, PEFC Sustainable Forest Management significantly and positively affects the company's competitiveness such as increased customer satisfaction, increased sales and decreased customer complaints.